Comparison of the Effect of Insulin with Metformin on Neonatal Outcome in Booked Patients with Gestational Diabetes Mellitus: Insulin vs Metformin in GDM: Neonatal Outcomes - Ishtiaque, Maria; Janjua, Mahham; Ashraf, Nomia; Choudhary, Saima; Iqbal, Tayyaba; Akhtar, Naheed (Pakistan Journal of Health Sciences, 2026)
Insulin has long been used as a treatment for gestational diabetes that is not well managed with diet. Metformin has been shown in several trials conducted in recent years to produce perinatal and obstetric results that are comparable to those of insulin. Studies have reported conflicting results regarding both modalities, and not all clinical recommendations support its usage. Objective: To compare neonatal outcomes in patients with metformin-treated gestational diabetes mellitus versus those with insulin-treated gestational diabetes mellitus. Methods: An observational study took place at the Obstetrics and Gynaecology Unit-III of Lady Willingdon Hospital, Lahore, during the time period starting from January 1, 2023, until December 1, 2023. One hundred and eighty-eight patients (94 in each group) were included in the study. In Group A, metformin tablets were given, and patients in Group B were given insulin. Outcome variables were measured as per the operational definition, respectively. Results: Patients receiving insulin therapy developed macrosomia more frequently (10.6% in the Metformin group vs. 23.4% in the Insulin group, p=0.029), along with hypoglycaemia (19.2% for Metformin vs. 33% for Insulin, p=0.031) and respiratory distress (9.6% Metformin vs. 20.2% Insulin, p=0.041) statistically often. Research showed no meaningful differences in findings between study groups regarding jaundice occurrence, together with intrauterine growth restriction (IUGR) and amniotic fluid measurements. Conclusions: In comparison to insulin, metformin is equally effective in preventing neonatal complications such as macrosomia, hypoglycaemia, and respiratory distress in women with gestational diabetes.